Q: What is (6x2) plus 3?

Write your answer...

Submit

Related questions

6x2 + 11x + 3 = 6x2 + 9x + 2x + 3 = 3x(2x + 3) + 1(2x + 3) = (2x + 3)(3x + 1)

Rearrange: 4x5 + 6x2 + 6x3 + 9 Group: 2x2 (2x3 + 3) + 3 (2x3 + 3) Simplify to get your answer: (2x2 + 3) (2x3 + 3)

The expression may be : 6x2 + 17x + 12 This factors as, 6x2 + 17x + 12 = (3x + 4)(2x + 3) Or, the expression could be : 6x2 - 17x + 12 This factors as, 6x2 - 17x + 12 = (3x - 4)(2x - 3)

9+6x2=21

6x2 + 9x = 0 3x(2x + 3) = 0 3x = 0 or 2x + 3 = 0 x = 0 or x = -3/2

6x2 + 10x = 2x(3x + 5)

6x2=12 2x-28=?

7X^3 Third degree polynomial.

7 + 24 ÷ (6x2) =7 + 24 ÷ 12 = 7 + 2 = 9

6x2-7x-3 = (3x+1)(2x-3)

No.

-3(2x + 1)(4 + 3x) = -3[8x + 6x2 + 4 + 3x] = -3[6x2 + 11x + 4] = -18x2 - 33x - 12.

x3 - 6x2 + 4x + 15 = (x - 3)(x - (3/2 + √29/2))(x - (3/2 - √29/2)) ⇒ roots are x = 3, x = 3/2 + √29/2 (≈ 4.19), or x = 3/2 - √29/2 (≈ -1.19)

(3x+1)(2x+4) = 6x2+4+2x+12x = 6x2+14x+4

(2x^2 - 5)(4x^3 + 3)

6x2+x-35 = (2x+5)(3x-7)

6x2 + 7x - 5 = (3x + 5)(2x - 1)

6x2+13x-5 = 0 (2x+5)(3x-1) = 0 x = -5/2 or x = 1/3

Simplifying 6x2 + 23x + 7 Reorder the terms: 7 + 23x + 6x2 Factor a trinomial. (7 + 2x)(1 + 3x) Final result: (7 + 2x)(1 + 3x)

First take out the common factor (4):4(6x2 + 2x + 1)6x2 + 2x + 1 cannot be factored, so 4(6x2 + 2x + 1) is as far as you can get with factoring.

(3x+1)(2x+2)

6x2-18x+12 = (6x-6)(x-2)

6x2-17x+7 = (2x-1)(3x-7) when factored

It is the same as: 3y24x+y26x2 that is if y2 and 6x2 means y2 and 6x2 respectively

If that's -17x, it factors to (3x - 4)(2x - 3)